Risk factors associated with cancer in the elderly. Medical Office 20 - Hernández Baño, Adnaloy; Díaz Pita, Gicela; Sparis Tejido, Mario Manuel; Núñez Díaz, Brenda de la Caridad; Pando Camejo, Dianelys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Cancer can be considered as a disease of the Older Adult since more than 65% of all malignant Neoplasms occur in this group, the risk of cancer usually increases with age due to a longer period of exposure to numerous carcinogenic elements.Objective: to characterize the risk factors associated with cancer in older adults belonging to the medical office 20 of the Pedro Borrás Astorga polyclinic, in the period September 2018 to May 2019.Method: an observational, analytical and cross-sectional study was conducted, the universe was constituted by 321 older adults, a sample of 90 older adults was selected, by non-probabilistic intentional sampling, theoretical, empirical and descriptive statistical methods were used.Results: there was a predominance of the age group 65-69 years, 64% of the female sex, 50% were normal weight, 40% were sedentary, 45% had up to 3 associated risk factors such as bad eating habits, smoking and alcoholism; family and personal pathological antecedents were arterial hypertension.Conclusions: several risk factors predominate in the elderly; this favors the appearance of a type of cancer. Actions aimed at the prevention and modification of risk factors are required to reduce the incidence of cancer and achieve a satisfactory longevity.